2019
DOI: 10.1038/s41598-019-50059-6
|View full text |Cite|
|
Sign up to set email alerts
|

Climate change, range shifts, and the disruption of a pollinator-plant complex

Abstract: Climate change has significant impacts on the distribution of species and alters ecological processes that result from species interactions. There is concern that such distribution shifts will affect animal-plant pollination networks. We modelled the potential future (2050 and 2070) distribution of an endangered migratory bat species (Leptonycteris nivalis) and the plants they pollinate (Agave spp) during their annual migration from central Mexico to the southern United States. Our models show that the overlap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 61 publications
0
47
0
2
Order By: Relevance
“…Plants and animals may lack adaptations to changes in wind conditions; similar to some species’ inability to adapt fast enough to recent changes in temperature and precipitation (e.g. Gómez‐Ruiz & Lacher Jr, 2019; Parmesan & Hanley, 2015; Radchuk et al., 2019). Therefore, the impacts of changes in wind patterns on plant communities will likely be dependent on interactions with microclimatic and/or topographic conditions, and will vary between habitat types and species groups.…”
Section: Discussionmentioning
confidence: 99%
“…Plants and animals may lack adaptations to changes in wind conditions; similar to some species’ inability to adapt fast enough to recent changes in temperature and precipitation (e.g. Gómez‐Ruiz & Lacher Jr, 2019; Parmesan & Hanley, 2015; Radchuk et al., 2019). Therefore, the impacts of changes in wind patterns on plant communities will likely be dependent on interactions with microclimatic and/or topographic conditions, and will vary between habitat types and species groups.…”
Section: Discussionmentioning
confidence: 99%
“…The mismatches modelled between bats and plants distributions were mainly caused by changes in plants distributions and richness patterns, highlighting that plants are more likely to suffer stronger effects of a changing environment (see Gómez‐Ruiz & Lacher, 2019). We showed that all plant groups analysed are shifting up in elevation tracking more suitable areas (see also Chen et al, 2011; Lenoir et al, 2008), which might be one of the causes of range contraction since mountain tops have a limited geographic extent.…”
Section: Discussionmentioning
confidence: 99%
“…These shifts towards cooler environments could be partially explained by the changes observed in temperature and precipitation variables across the country, where temperate habitats mostly located in highland areas offer and are likely to continue to offer colder and moister environments compared to the lowlands (Challenger & Soberón, 2008; Rzedowski, 2006). In fact, previous studies exploring the effects of past and future climate on plant communities highlight a general trend for plant species to shift towards higher elevations (Chen et al, 2011; Gómez‐Ruiz & Lacher, 2019; Mastretta‐Yanes et al, 2015; Salick et al, 2019). Chen et al (2011) estimated that, on average, species shifted to higher elevations at a median rate of 11 m per decade, but such shifts are dependent on the species functional traits.…”
Section: Discussionmentioning
confidence: 99%
“…There are several nestedness indices, of which nestedness metric based on overlap and decreasing fill (NODF) is considered the most robust [117]. expect that pathogen spread within a pollinator population or interspecific spillover may be reduced or exacerbated by: (i) invasions by novel species or subspecies [17] (Figure 1C); (ii) the extirpation of pre-existing populations or species [62] (Figure 1C); (iii) modification of the relative abundance of species and dominant interactions [63] (Figure 1D); (iv) disruption of species' phenology [64,65] (Figure 1D); (v) shifting species distributions at landscape, regional, or global levels [62]; or (vi) changing species physiology, altering disease resistance, infectivity, or virulence [17,66] (Figure 1E). While scientific and policy awareness of pressures on wild pollinators has increased and led to regulations at various levels protecting pollinators and their habitats, less regulatory…”
Section: Box 1 Key Network Metrics Affecting Pathogen Transmissionmentioning
confidence: 99%
“…Additionally, pollinator forage plants may be extirpated or produce less flowers or lower-quality floral rewards under changed climatic circumstances [73], causing nutritional stress and higher susceptibility of hosts [74]. Phenological or spatial mismatch of species interactions [64,75] due to life-history differences in tracking climate changes, or climate-induced species extirpations, or range shifts, may alter host activity and species relations [62,76]. Such mismatches, extinctions, and subsequent rewiring of networks [53,75], may change the prevalence of pathogens or parasites in pollinator communities and pathways to infection [77] (Figure 1D).…”
Section: Mechanistic Process-oriented Modelling Of Wild Pollinator Diseasementioning
confidence: 99%